2009
DOI: 10.1007/s00280-009-0941-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of gemcitabine plus oxaliplatin with and without rituximab as salvage treatment for transplant-ineligible patients with refractory/relapsing B-cell lymphoma

Abstract: Both regimes showed good tolerability and appealing response rates. FFS was more prolonged in R-GEMOX, but patients continuously relapsed without a clear plateau on survival curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…They confirmed good response rates with an ORR of 78% and a complete response rate of 50% for patients treated with R-GemOx, with mainly hematologic toxicity. 9 As in the CORAL trial, the cell of origin was not found to be a prognostic marker for second-line treatment of DLBCL. In this series of the 35 evaluable cases, we did not evidence a prognostic impact of the cell of origin phenotype according to Hans' algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They confirmed good response rates with an ORR of 78% and a complete response rate of 50% for patients treated with R-GemOx, with mainly hematologic toxicity. 9 As in the CORAL trial, the cell of origin was not found to be a prognostic marker for second-line treatment of DLBCL. In this series of the 35 evaluable cases, we did not evidence a prognostic impact of the cell of origin phenotype according to Hans' algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Eight cycles were planned if patients reached at least a partial response after four cycles. No dose adjustment was planned in the event of hematologic toxicity, but cycles were postponed until the absolute neutrophil count reached 1.0x10 9 /L and the platelet count reached 100x10 9 /L. The dose of oxaliplatin was adjusted in the event of peripheral neuropathy, as previously described.…”
Section: Chemotherapy and Dose Adjustmentsmentioning
confidence: 99%
“…It has activity and is well tolerated in elderly patients, [64][65][66] but long-term results in patients with prior exposure to rituximab are not satisfactory. Therefore, whenever possible, I treat my elderly patients with relapsing DLBCL within prospective trials, which try to evaluate the role of new antibodies and small molecules in this setting.…”
Section: Treatment Of Relapsed and Refractory Diseasementioning
confidence: 99%
“…331 Rituximab with other regimens has also been effective in patients with relapsed or refractory DLBCL. [332][333][334][335][336][337][338] An international Intergroup study (CORAL study) compared R-ICE and DHAP (dexamethasone, cisplatin, and cytarabine; R-DHAP) followed by ASCR in patients with relapsed DLBCL. 339 No significant differences were seen in the 3-year eventfree (26% vs. 35%) and overall survival rates (47% vs. 51%) between R-ICE and R-DHAP.…”
Section: Relapsed or Refractory Diseasementioning
confidence: 99%